2022
DOI: 10.3390/drones7010005
|View full text |Cite
|
Sign up to set email alerts
|

Using Drones with Thermal Imaging to Estimate Population Counts of European Hare (Lepus europaeus) in Denmark

Abstract: Drones equipped with thermal cameras have recently become readily available, broadening the possibilities for monitoring wildlife. The European hare (Lepus europaeus) is a nocturnal mammal that is closely monitored in Denmark due to populations declining since the mid-1900s. The limitations of current population-assessment methods, such as, spotlight counts and hunting game statistics, could be overcome by relying on drone surveys with thermal imaging for population counts. The aim of this study was to investi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…While spotlights also rely on direct line of sight, almost all endotherms detected with spotlights were flying or running from their roost site upon detection, and would most likely be detected regardless of vegetation openness when they move into an open area. It is also possible that endotherm abundance was different between years and sites due to vegetation structure, grazing regimes or rainfall, and these variables may have interacted to influence detection probabilities (Broadley et al, 2019;Davis et al, 2021;Povlsen et al, 2023;Winter et al, 2005).…”
Section: Difference In Detection Probability Between Monitoring Periodsmentioning
confidence: 99%
“…While spotlights also rely on direct line of sight, almost all endotherms detected with spotlights were flying or running from their roost site upon detection, and would most likely be detected regardless of vegetation openness when they move into an open area. It is also possible that endotherm abundance was different between years and sites due to vegetation structure, grazing regimes or rainfall, and these variables may have interacted to influence detection probabilities (Broadley et al, 2019;Davis et al, 2021;Povlsen et al, 2023;Winter et al, 2005).…”
Section: Difference In Detection Probability Between Monitoring Periodsmentioning
confidence: 99%
“…Recent technological advances, such as better battery capacity, improved sensors, and lower cost, have accelerated the applications of aerial drones, also known as uncrewed or unmanned aerial vehicles (UAV), unmanned aerial systems (UAS) and remotely piloted aircraft systems (RPAS), in the field of ecology and wildlife monitoring [22][23][24][25][26][27][28][29][30]. Especially multirotor drones, as opposed to fixed-winged drones, equipped with thermal infrared (TIR) cameras have proven to be a useful tool for monitoring cryptic and nocturnal species, on par with spotlight methods [3,25,26,[30][31][32][33][34][35][36][37][38].…”
Section: Drones In Wildlife Monitoringmentioning
confidence: 99%
“…Their study also suggested that angles other than 90 • of the drone-mounted sensors during surveys should be examined [35,39]. Povlsen et al [24] conducted a drone survey concurrently with a spotlight count. This was performed by flying at a 60 m altitude, with the camera recording directly downwards, while the drone was flying autonomously in a predetermined flight path, covering the same transects surveyed with spotlights.…”
Section: Drones In Wildlife Monitoringmentioning
confidence: 99%
“…Povlsen et al [28] flew in predetermined flight paths at 60 m altitude with a DJI Mavic 2 Enterprise Advanced with the thermal camera pointing directly down (90 • ), covering the transects that were simultaneously surveyed, monitoring hare, deer, and fox. Using transect counting, it was possible to spot roughly the same number of animals as the traditional ground-based spotlight count [28]. However, this method covered a relatively small area per flight, and required post-processing of the captured imagery, still making it time-consuming.…”
Section: Mean Average Precisionmentioning
confidence: 99%